PENGARUH TEKNIK FORUM TERHADAPMENULIS BERITA DI KELAS VIII SMP NEGERI 1 TIGANDERKET TAHUN PELAJARAN 2012/2013 - SRI ULINA BANGUN (Kode : Jurnal Bahasa, 2013)
This study aims to determine the effect of forum technique to writing news by the VIII grade of the students of SMP Negeri 1 Tiganderket in academic year 2012/2013, which amounted to 149 students and that a sample as many as 40 students. Sampling was done by determining the class to be representative of the population studied. The research method used was experimental method to the study design models One Group Pre-test Post-test design that is only implemented in one class (group) only. Inthe design of these measurements were performed twice, before experiment and after experiment. Measurements were carried out before the experiment is called the pretest and post-experiment measurements called post-test. From the data processing, the value of the average pretest 70.65, standard deviation 2.12. The average value of posttest 78, 80, standard deviation 10, 38. Based on the normality test, the results ofpre-test and post-test revealed normal distribution. Then, based on homogeneity test revealed that the samples come from a homogeneous population. After testing for normality and homogeneity do, then it transpired t0 of 3.50. Furthermore, in consultation with the table tt the 5% significance level with df = n -1 = 40 -1 = 39 obtained significant level of 5% is 2.02. Based on the calculations that have been done, it is known t0 > tt, 3.50 > 2.02. Thus H0 (null hypothesis) is rejected and Ha(alternative hypothesis) is accepted. This proves that there is the Effects of Using forum technique in writing news by the students VIII grade of SMP Negeri 1 Tiganderket in Academic Year 2012/2013.Keywords: Forum Technique, Writing News